TEACHING OF ACCOUNTING IN SCHOOLS OF ENGINEERING. - White, James C. (The Accounting Review, 1930)
Abstract The scope of the engineer is changing. Today's engineer must not only know his chemistry, physics, and mathematics; he must also be familiar with finance, labor problems, and accounting. One finds the engineer as the chief executive of many successful organizations. In such a capacity, he must be more than the master craftsman; he must be the able administrator of functions whose technologies are widely different. Now engineering clearly falls under the general function of management; yet management is more than engineering. To give a general list of the fields of management there are in broad general terms: finance, personnel, public relations, purchasing, traffic, storage, sales, design, production. Certainly engineering is most closely related to production, rather than to the others; and there is where it belongs. Yet production management and engineering are not parallel terms. The engineer solves technical problems of design – of product, of machinery and equipment, of plant, and of operation – but the production management must coordinate these, and cooperate with managers of finance, personnel, public relations, purchasing traffic, storage, and sales, in order to keep production going in balance with the other units of the organization.